Membangun Sekolah Ramah Diversitas: Implementasi Pendidikan Inklusif Di Madrasah Ibtidaiyyah - Nasir, Muhammad (El-Miaz: Jurnal Pemikiran dan Pendidikan Dasar, 2024)
Inclusive education is an educational approach that emphasizes the full participation of all students, including those who have special learning needs, in regular school learning. The implementation of inclusive education at MI AL-Ishlah Jepara (MI) is an important step in realizing a diversity-friendly and inclusive school, where every child can learn and develop optimally according to their individual potential and needs. This journal aims to discuss the concept of inclusive education and its relevance to building diversity-friendly schools in MI. This journal will also examine the strategies and steps for implementing inclusive education in MI, as well as the various challenges and opportunities faced in its implementation. Inclusive education is an important focus in the world of modern education, aiming to create a friendly learning environment for all children, regardless of their background, abilities and needs. The implementation of inclusive education at MI Al-Ishlah Jepara (MI) is a crucial step in building a generation that is tolerant, open and appreciates diversity. This research uses grounded theory methodology to examine the process of implementing inclusive education in MI, identifying factors that influence its success, and producing a theory about how to build diversity-friendly schools.